2018
DOI: 10.3389/fpsyg.2018.01745
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Humor in Social Interaction in People With Intellectual Disabilities: A Systematic Review of the Literature

Abstract: Background: Humor, both producing and appreciating, underpins positive social interactions. It acts as a facilitator of communication. There are clear links to wellbeing that go along with this form of social engagement. However, humor appears to be a seldom studied, cross-disciplinary area of investigation when applied to people with an intellectual disability. This review collates the current state of knowledge regarding the role of humor behavior in the social interactions of people with intellectual disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The stand-up comedy approach is also more accessible for creating humorous situations. Humour is an integral part of social interaction, and, in some caring contexts, it serves as a coping strategy with mental and physical health effects [39]. According to [40], technologies such as robots and hand-held equipment could represent a tool to bring humour and joy into the everyday lives and events of older adults through human-robot interaction.…”
Section: Bodies and Genders In Interactionmentioning
confidence: 99%
“…The stand-up comedy approach is also more accessible for creating humorous situations. Humour is an integral part of social interaction, and, in some caring contexts, it serves as a coping strategy with mental and physical health effects [39]. According to [40], technologies such as robots and hand-held equipment could represent a tool to bring humour and joy into the everyday lives and events of older adults through human-robot interaction.…”
Section: Bodies and Genders In Interactionmentioning
confidence: 99%
“…A meta-analysis (k = 39, n = 15,177) exploring humour in romantic relationships found six humour types positively associated to relationship satisfaction, and five negatively associated, with associations to relationship satisfaction much larger in partner-perceived humour than in self-reported humour [2]. Social humour was found to serve valuable 'social, developmental, and emotional wellbeing functions' in a systematic review of people with intellectual disabilities and their carers (k = 26, n = 1,351) [38]. An ethnographic study (n = 57) concluded humour has important social functions as a social lubricant, a coping mechanism, and a way to negotiate power [95].…”
Section: Social: Humour Researchmentioning
confidence: 99%
“…Most social media posts about COVID-19 tend to be primarily negative or serious, whereas humorous posts can deal with the same serious issue by pointing out "the funny or ironic aspects of a situation" (Phillips-Kumaga et al 2022). The sense of humour can facilitate the restructuring of a crisis situation so it is less stressful (Abel 2002), thereby making people receptive to messages which they would otherwise not have been open to (Ogba 2021) hence promoting positive social interaction and solidarity (Chadwick & Platt 2018;Uwen & Ushie 2022). The general posts mainly deal with topics such as COVID-19 tests and deaths (Ahmed et al 2021), misconceptions and complaints about COVID-19 control (Kwok et al 2021), the spread of the virus, and bans and orders (Norstrom & Sarna 2021).…”
Section: Introductionmentioning
confidence: 99%